Achieving Universal Access to ID : Gender-based Legal Barriers Against Women and Good Practice Reforms - Hanmer, Lucia; Elefante, Marina (World Bank, Washington, DC, 2019)
Proof of identity is vital in modern society. Individuals need identity documents to participate in many aspects of civil, political, and economic life. These include obtaining a job in the formal sector, opening a bank account, borrowing from a financial institution, and owning a property or a business in addition to traveling, voting, and gaining access to health and social welfare services. For women and girls, legal identity is a stepping stone to empowerment, agency, and freedom of movement. Hence, it is a vital enabler of Sustainable Development Goal (SDG). Achieve gender equality and empower all women and girls. However, many women and girls do not have access to legal identity. Globally, it is estimated that 1 billion people are unable to prove their identity, and millions more have forms of identification that cannot be reliably verified or authenticated (World Bank 2015). This paper explores how gender-based legal differences and nationality laws limit women’s ability to obtain identification for themselves, their children, and, in the case of nationality laws, their spouses too. It brings together data and analysis produced by agencies working on legal barriers that pertain to their mandates, for example, the United Nations Children’s Fund (UNICEF) on birth registration, the United Nations High Commissioner for Refugees (UNHCR) on statelessness, and the evidence produced by the World Bank Group’s Women, Business and the Law and other legal sources. Its aim is to provide a comprehensive overview of the extent of gender-based legal barriers against women to ID and what is known about their impact on women, children, and excluded groups.